Biology and population dynamics of Scaeva albomaculata (Diptera: Syrphidae) in almond orchards of Shahrekord, Iran - S. H. Nourbakhsh; E. Soleymannejadian; A. R. Nemti (نامه انجمن حشره‌شناسی ایران, 2008)
Biology of Scaeva albomaculata (Macquart) was investigated on Brachycaudus amygdalinus (Schouteden) as a prey in laboratory conditions (20 ± 2 ºC and 45 ± 5 % RH). Developmental times were 2.57 ± 0.098, 1.57 ± 0.072 and 4.3 ± 0.085 days for the first, second and third instar larvae, respectively. The first and second instar larvae of syrphid fly consumed 21.7 ± 0.87 and 35.1 ± 1.25 the first and second nymphs, respectively, whereas the third instar larvae consumed 613.2 ± 18.43 alate nymphs of B. amygdalinus. Adults of syrphid flies mostly emerged in early morning. Population dynamics of eggs and larvae and larval behavior were studied from emergence time (early March) to late October during 2001-2004 in two regions (Shahrekord and Shorab-Saghir). In natural conditions, the larvae that completed their growth left the almond twigs and pupated at a depth of 3-5 cm below the soil surface. The most important natural enemies of S. albomaculata larvae were identified as Diplazon laetatorius (Fabricius) (Hym.: Ichneomonidae) and Dotriothorax sp. (Hym.: Encyrtidae), which parasitized 34% and 5% of the larvae, respectively. These parasitoids emerged from pupae of S. albomaculata. Another mortality agent was an unknown pathogen, which caused the body content of the pupae to become a milky liquid.